ANALISIS STRUKTUR MUSIK DAN TEKNIK BERMAIN BIOLA FOUR SEASON œWINTER KARYA KOMPONIS ANTONIO VIVALDI - Simangunsong, Christine (Grenek: Jurnal Seni Musik, 2017)
This study aims to determine how the structure of music andviolin technique Four Season "Winter" by composer Antonio Vivaldi.In the discussion of this study used the theories related to researchtopics such as Antonio Vivaldi biography, analytical understanding,understanding of musical forms, musical structure and technique ofplaying the violin. The method used by the researchers in this study isdescriptive-qualitative method. The sample in this study such as thesheet music and videos of Four Season "Winter" by composer AntonioVivaldi. The techniques of data collection in this research are workinglaboratory analysis the melody of violin instrument like musicalstructure and technique of playing the violin and literature studyconducted at the Laboratory of the Department of Music Arts, Facultyof Languages and Arts, State University of Medan. From the results ofthis study can be obtained structure of music Four Season "Winter" bycomposer Antonio Vivaldi has 63 bars with 12 motifs includingoriginal motive literal replications and development, up and downsequence, bridges, enlargement of the interval, 10 phrases and is a 3-part song form complex / major played by violin playing techniques asdiverse namely legato, staccato, trill, double stops, and sforzando andusing the dynamic crescendo, mezzo forte, forte, piano, with the righthand position of mixed fingering position of the I-VII. Interpretationof the Four Seasons "Winter" tells the eerie atmosphere transitionalclimate when winter freeze with the sound of the wind through thestrains indicated cruel instrument tones on the violin.